Comparación mecánica de dos sistemas de fijación interna rígida utilizados en la fijación de fracturas faciales (estudio in vitro) (2016)
ABSTRACT: The use of titanium miniplates is the gold standard in the treatment of facial fractures. A Colombian company has developed a system of osteosynthesis miniplates for the treatment of facial fractures, which was chemically and mechanically compared with an imported system. Methods: comparative in-vitro tests were carried out to analyze the chemical composition and the biomechanical behavior of the national and imported systems. A sample of 36 items was selected, including 24 miniplates and 12 screws, in order to mechanically assess their materials by means of tensile and flexural tests for the plates and torque strength tests for the screws, and to perform a microscopic analysis of the chemical composition of the plates of both brands by means of scanning electron microscopy (SEM) and Energy Dispersive Spectroscopy (EDS). Results: The findings showed that there are no major differences in terms of the chemical composition and the biomechanical behavior of the implants of both brands (national and imported) when assessing plates and screws separately. Conclusions: the results showed a higher content of titanium in the material of national plates; however, the mechanical properties of both brands are very similar. Taking into account the material’s biomechanical characteristics, either system is a good choice when selecting a device for rigid internal fixation of facial fractures.